Accelerating Downstream Agribusiness: An Analysis of Factors Driving Millennial Farmers' Interest in Innovative Yogurt Entrepreneurship - Muh. Nur Khamid; lutfan makmun; Wida Wahidah Mubarokah; Haris Tri Wibowo; Early Nora Permata (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to analyze the driving factors of millennial farmers' entrepreneurial interest in the innovative processing of cow's milk into Ambon banana yoghurt in Boyolali Regency. The local dairy farming sector faces challenges in optimising the added value of derivative products due to millennial farmers' limited knowledge. Using a descriptive quantitative approach, the study was conducted in Boyolali Regency, Central Java Province, Indonesia, from April to June 2025, with 33 respondents selected through purposive sampling. Data were collected through interviews, observations, and questionnaires, then analyzed using descriptive analysis and multiple linear regression (SPSS). The descriptive analysis showed that millennial farmers' interest was relatively high (83.83%). The regression analysis identified that simultaneously, age, education level, and experience had a very significant effect on entrepreneurial interest (R2=0.713; p<0.01). Partially, education level and experience were the main determinants, while age was not a significant factor. The effectiveness of extension services was considered very effective (81.13%). The study concludes that cognitive factors (education and experience) play a crucial role in fostering interest in innovation-based entrepreneurship among millennial farmers. The study's results recommend a structured extension program to accelerate the downstreaming of agribusiness products. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 4: Quality EducationSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and Infrastructure